1978
DOI: 10.1159/000237762
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of 6-Cyclohexyl-l-hydroxy-4-methyl-2(1H)-pyridone Ethanolamine Salt (Hoe 296)

Abstract: Mode of action studies were made with Hoe 296, a new synthetic antimycotic, mainly in Candida albicans. The specific parameters examined included possible effects on (i) osmotic fragility, (ii) respiration, (iii) uptake and incorporation of radioactive leucine and adenine, and (iv) leakage or efflux of intracellular K+ and other materials. As a result, fungitoxic activity of Hoe 296 appears to be attributed to inhibition of uptake of precursors of macromolecular syntheses from the medium. Uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 6 publications
0
24
0
2
Order By: Relevance
“…Studies in C. albicans have shown that ciclopirox alters the structure of cell membranes [17], [49], [50]. Indeed, 97% of ciclopirox administered to C. albicans was bound to cell membranes and organelles, with very little drug in the cytoplasm [50].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in C. albicans have shown that ciclopirox alters the structure of cell membranes [17], [49], [50]. Indeed, 97% of ciclopirox administered to C. albicans was bound to cell membranes and organelles, with very little drug in the cytoplasm [50].…”
Section: Resultsmentioning
confidence: 99%
“…Another feature that influences the clinical potency of the drug is its steep dose-response curve (16). Most of the studies dealing with the mode of action of this drug were published approximately 20 years ago, at the time that ciclopirox olamine was synthesized and introduced into clinical therapy (16,17,23,33,40,49). When the drug became more frequently used, the results of many investigations about its efficacy and comparisons of its clinical effectiveness with those of other antimicrobial agents were published (25); however, the primary mode of action was rarely investigated.…”
mentioning
confidence: 99%
“…More than 97% of the accumulated drug is bound largely irreversibly to different cell structures and organelles such as the cell membrane, cell wall, mitochondria, microsomes, and ribosomes, while only small amounts are found in the cytosolic fraction. The drug is neither metabolized nor degraded (49). Furthermore, it was demonstrated that ciclopirox olamine causes inhibition of protein, RNA, and DNA synthesis in growing fungal cells, possibly by blocking the uptake of precursors of the macromolecules or by blocking the uptake of essential ions such as potassium ions and phosphates (33).…”
mentioning
confidence: 99%
“…[10][11][12] Unlike the imidazoles and allylamines, which inhibit synthesis of fungal cell walls, ciclopirox complexes polyvalent cations, thus inhibiting metal-dependent enzymes including those responsible for peroxide degradation in the fungal cell. 13 There is some evidence of antibacterial and antiinflammatory activity. 11,14 The potent antipityrosporal effects of ciclopirox combined with its tolerability and lack of toxic effects make it an ideal alternative to existing antifungal agents both for treatment and prophylaxis of seborrheic dermatitis.…”
mentioning
confidence: 99%